Sulfur Mediated Alleviation of Mn Toxicity in Polish Wheat Relates to Regulating Mn Allocation and Improving Antioxidant System - Sheng, Huajin; Zeng, Jian; Liu, Yang; Wang, Xiaolu; Wang, Yi; Kang, Houyang; Fan, Xing; Sha, Lina; Zhang, Haiqin; Zhou, Yonghong (Frontiers in Plant Science, 2016)
Sulfur (S) is an essential macronutrient that has been proved to play an important role in regulating plant responses to various biotic and abiotic stresses. The present study was designed to investigate the effect of S status on polish wheat plant response to Mn toxicity. Results showed that Mn stress inhibited plant growth, disturbed photosynthesis and induced oxidative stress. In response to Mn stress,polish wheat plant activated several detoxification mechanisms to counteract Mn toxicity, including enhanced antioxidant defense system, increased Mn distribution in the cell wall and upregulated genes involved in S assimilation. Moderate S application was found to alleviate Mn toxicity mainly by sequestering excess Mn into vacuoles, inhibiting Mn translocation from roots to shoots, stimulating activities of antioxidant enzymes and enhancing GSH production via upregulating genes involved in S metabolism. However, application of high level S to Mn-stressed plants did not significantly alleviated Mn toxicity likely due to osmotic stress. In conclusion, moderate S application is beneficial to wheat plants against Mn toxicity, S exerts its effects via stimulating the antioxidant defense system and regulating the translocation and subcellular distribution of Mn, in which processes GSH plays an indispensable role.